2018
DOI: 10.1016/j.oregeorev.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of magmatic-hydrothermal and metamorphic fluids and the origin of peribatholitic Sn vein-type deposits in Rwanda

Abstract: The fluid sources of granite-related Sn-quartz vein deposits are commonly obscured by fluid mixing or fluid-rock interactions. As a result, fluid inclusions, minerals and isotopes in these veins indicate an intermediate composition between magmatic and metamorphic, but the degree of mixing between Highlights  Peribatholitic Sn-quartz veins often show secondary overprinting signatures.  Fluid mixing was quantified by muscovite and fluid inclusion geochemistry  Fluid mixing plays an important role in the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 75 publications
(137 reference statements)
0
13
0
2
Order By: Relevance
“…14). Such a trend has been recognized in other similar systems worldwide (Shieh and Zhang, 1991;Bettencourt et al, 2005;Chicharro et al, 2016;Van Daele et al, 2018). For example, in the Dajishan Mine (Jiangxi Province, Southeast China), the fluid δD values increase (at nearly constant δ 18 O) from the magmatic (defined by minerals from the muscovite granite) to the main Sn-W ore stage (defined by minerals from the veins).…”
Section: Temperatures and Fluid Isotopic Compositionsmentioning
confidence: 59%
“…14). Such a trend has been recognized in other similar systems worldwide (Shieh and Zhang, 1991;Bettencourt et al, 2005;Chicharro et al, 2016;Van Daele et al, 2018). For example, in the Dajishan Mine (Jiangxi Province, Southeast China), the fluid δD values increase (at nearly constant δ 18 O) from the magmatic (defined by minerals from the muscovite granite) to the main Sn-W ore stage (defined by minerals from the veins).…”
Section: Temperatures and Fluid Isotopic Compositionsmentioning
confidence: 59%
“…Thermodynamic calculations have shown that high Sn concentrations (100s to 1000s ppm) can be transported as Sn chloride complexes in acidic and reduced hydrothermal fluids rapidly flowing along rock-buffered conduits (Heinrich, 1990). Such high concentrations have been measured in individual primary fluid inclusions hosted in peraluminous granites and associated cassiterite-bearing quartz veins (Audétat et al, 2000a(Audétat et al, ,b, 2008Borisova et al, 2012;Harlaux et al, 2017;Van Daele et al, 2018;Korges et al, 2018;Legros et al, 2019). The coexistence and intergrowth of Tur 3 with cassiterite suggest the destabilization of Sn-Cl complexes in the hydrothermal fluid, which is decisive for cassiterite deposition (Schmidt, 2018).…”
Section: Tin Content In Tourmaline and Implications For Cassiterite Mineralizationmentioning
confidence: 99%
“…Formation of high-grade tin deposits from initially reduced and acidic magmatic fluids is favored by oxidation and acid neutralization reactions allowing precipitation of cassiterite (Heinrich, 1990). Among the different possible mechanisms for hydrothermal tin mineralization, fluid mixing between reduced, Sn-rich magmatic fluid and oxidized external fluids (meteoric or metamorphic) has generally been invoked as the most efficient process for forming peri-granitic hydrothermal tin deposits, based on fluid inclusion and stable isotope data (e.g., Audétat et al, 2000a,b;Vallance et al, 2001;Fekete et al, 2016;Legros et al, 2019;Van Daele et al, 2018). The progressive decrease of the (Eu/Eu*)N ratio (from 20 to 2) correlated with an increase in the Sn contents (from 10s to >1000 ppm) observed from Tur 1 to Tur 3 (Fig.…”
Section: Tin Content In Tourmaline and Implications For Cassiterite Mineralizationmentioning
confidence: 99%
“…Comme le Cs est très soluble dans les fluides magmatiques-hydrothermaux (London, 2005b), il est souvent supposé que les micas enrichis en Cs précipitent d'un système de magma saturé de fluide (e.g. Černý et al, 2012;Dewaele et al, 2016;Van Daele et al, 2018). En d'autres termes, l'augmentation de Cs dans les micas pourrait théoriquement être modélisée dans un système cristal-magmafluide (e.g.…”
Section: Relation Co-génétique Entre Le Leucogranite Gr5 Et Les Pegmaunclassified